2001
DOI: 10.1016/s0277-5387(01)00633-7
|View full text |Cite
|
Sign up to set email alerts
|

Single crystal EPR determination of the spin Hamiltonian parameters for Fe8 molecular clusters

Abstract: We use a multi-high-frequency resonant cavity technique to obtain EPR spectra for single crystal samples of the biaxial molecular magnet Fe 8 [(tacn) 6 O 2 (OH) 12 ]Br 8 ·9H 2 O (Fe 8 ). By performing measurements at many closely spaced frequencies, we are able to extrapolate data back to zero magnetic field and, thereby, obtain accurate estimates of the zero-field splittings. Furthermore, from the (low-) field dependence of these splittings, with the magnetic field parallel to the easy axis, we can directly m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
59
0

Year Published

2002
2002
2014
2014

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 39 publications
(63 citation statements)
references
References 24 publications
4
59
0
Order By: Relevance
“…Indeed, even for aligned polycrystals, significant discrepancies can be noted between the observed and calculated EPR transitions, with respect to both the peak positions and intensities, as well as the line shapes and widths [33]. As an example, it has been reported in [33] that the linewidths in Fe 8 Br approximately scale as M 2 S , whereas our earlier studies [29,37] have shown a dominant linear dependence of the linewidths on M S , both for Fe 8 Br and Mn 12 −ac. This fact, along with the asymmetric lineshapes observed in high field EPR studies, may account for differences in the spin Hamiltonian parameters deduced by single-pass (i.e.…”
Section: Introductionmentioning
confidence: 61%
See 4 more Smart Citations
“…Indeed, even for aligned polycrystals, significant discrepancies can be noted between the observed and calculated EPR transitions, with respect to both the peak positions and intensities, as well as the line shapes and widths [33]. As an example, it has been reported in [33] that the linewidths in Fe 8 Br approximately scale as M 2 S , whereas our earlier studies [29,37] have shown a dominant linear dependence of the linewidths on M S , both for Fe 8 Br and Mn 12 −ac. This fact, along with the asymmetric lineshapes observed in high field EPR studies, may account for differences in the spin Hamiltonian parameters deduced by single-pass (i.e.…”
Section: Introductionmentioning
confidence: 61%
“…Orientation of Mn 12 −ac crystal was straightforward, due to the fact that its easy axis is defined by the needle axis of the sample. Alignment of the Fe 8 Br crystal necessitated measurements at many angles [29]. All of the data presented in this paper were obtained with the DC magnetic field aligned approximately parallel to the samples' easy axes (hard axis data are presented elsewhere [26,29]).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations